Molecular-resolution imaging of pentacene on KCl(001) - Neff, Julia L.; Götzen, Jan; Li, Enhui; Marz, Michael; Hoffmann-Vogel, Regina (Beilstein Journal of Nanotechnology, 2012)
The growth of pentacene on KCl(001) at submonolayer coverage was studied by dynamic scanning force microscopy. At coverages below one monolayer pentacene was found to arrange in islands with an upright configuration. The molecular arrangement was resolved in high-resolution images. In these images two different types of patterns were observed, which switch repeatedly. In addition, defects were found, such as a molecular vacancy and domain boundaries.
Keywords: KCl; molecular growth; pentacene; scanning force microscopy; self-assembly

(untitled) - Rosei, F.; Schunack, M.; Naitoh, Y.; Jiang, P.; Gourdon, A.; Laegsgaard, E.; Stensgaard, I.; Joachim, C.; Besenbacher, F. (Progr. Surf. Sci., 2003)
Proceedings of the IXth Symposium on Surface Physics, Trest Castle 2002.

(untitled) - Kudernac, T.; Lei, S.; Elemans, J. A. A. W.; De Feyter, S. (Chem. Soc. Rev., 2009)

(untitled) - Nony, L.; Gnecco, E.; Baratoff, A.; Alkauskas, A.; Bennewitz, R.; Pfeiffer, O.; Maier, S.; Wetzel, A.; Meyer, E.; Gerber, C. (Nano Lett., 2004)

(untitled) - Kunstmann, T.; Schlarb, A.; Fendrich, M.; Wagner, T.; Möller, R.; Hoffmann, R. (Phys. Rev. B, 2005)

(untitled) - Burke, S. A.; Mativetsky, J. M.; Hoffmann, R.; Grütter, P. (Phys. Rev. Lett., 2005)

(untitled) - Burke, S. A.; Ji, W.; Mativetsky, J. M.; Topple, J. M.; Fostner, S.; Gao, H.-J.; Guo, H.; Grütter, P. (Phys. Rev. Lett., 2008)

(untitled) - Dienel, T.; Loppacher, C.; Mannsfeld, S. C. B.; Forker, R.; Fritz, T. (Adv. Mater., 2008)

(untitled) - Pawlak, R.; Nony, L.; Bocquet, F.; Oison, V.; Sassi, M.; Debierre, J.-M.; Loppacher, C.; Porte, L. (J. Phys. Chem. C, 2010)

(untitled) - Such, B.; Trevethan, T.; Glatzel, T.; Kawai, S.; Zimmerli, L.; Meyer, E.; Shluger, A. L.; Amijs, C. H. M.; de Mendoza, P.; Echavarren, A. M. (ACS Nano, 2010)

(untitled) - Hinaut, A.; Lekhal, K.; Aivazian, G.; Bataillé, S.; Gourdon, A.; Martrou, D.; Gauthier, S. (J. Phys. Chem. C, 2011)

(untitled) - Körner, M.; Loske, F.; Einax, M.; Kühnle, A.; Reichling, M.; Maass, P. (Phys. Rev. Lett., 2011)

(untitled) - Dimitrakopoulos, C. D.; Purushothaman, S.; Kymissis, J.; Callegari, A.; Shaw, J. M. (Science, 1999)

(untitled) - Witte, G.; Wöll, C. (J. Mater. Res., 2004)

(untitled) - Ruiz, R.; Nickel, B.; Koch, N.; Feldman, L. C.; Haglund, R. F.; Kahn, A.; Scoles, G. (Phys. Rev. B, 2003)

(untitled) - Thayer, G. E.; Sadowski, J. T.; Meyer zu Heringdorf, F.; Sakurai, T.; Tromp, R. M. (Phys. Rev. Lett., 2005)

(untitled) - Mayer, A. C.; Kazimirov, A.; Malliaras, G. G. (Phys. Rev. Lett., 2006)

(untitled) - Zheng, Y.; Wee, A. T. S.; Chandrasekhar, N. (ACS Nano, 2010)

(untitled) - Götzen, J.; Käfer, D.; Wöll, C.; Witte, G. (Phys. Rev. B, 2010)

(untitled) - Lukas, S.; Witte, G.; Wöll, C. (Phys. Rev. Lett., 2001)

(untitled) - Söhnchen, S.; Lukas, S.; Witte, G. (J. Chem. Phys., 2004)

(untitled) - France, C. B.; Schroeder, P. G.; Forsythe, J. C.; Parkinson, B. A. (Langmuir, 2003)

(untitled) - Käfer, D.; Ruppel, L.; Witte, G. (Phys. Rev. B, 2007)

(untitled) - Mete, E.; Demiroğlu, I.; Fatih Danışman, M.; Ellialtıoğlu, S. (J. Phys. Chem. C, 2010)

(untitled) - Götzen, J.; Lukas, S.; Birkner, A.; Witte, G. (Surf. Sci., 2011)

(untitled) - Kawai, S.; Pawlak, R.; Glatzel, T.; Meyer, E. (Phys. Rev. B, 2011)

(untitled) - Dimitrakopoulos, C. D.; Malenfant, P. R. L. (Adv. Mater., 2002)

(untitled) - Yoshida, H.; Inaba, K.; Sato, N. (Appl. Phys. Lett., 2007)

(untitled) - Campbell, R. B.; Robertson, J. M.; Trotter, J. (Acta Crystallogr., 1962)

(untitled) - Siegrist, T.; Kloc, C.; Schön, J. H.; Batlogg, B.; Haddon, R. C.; Berg, S.; Thomas, G. A. (Angew. Chem., Int. Ed., 2001)

(untitled) - Wu, J. S.; Spence, J. C. H. (J. Appl. Crystallogr., 2004)

(untitled) - Kiyomura, T.; Nemoto, T.; Ogawa, T.; Minari, T.; Yoshida, K.; Kurata, H.; Isoda, S. (Jap. J. Appl. Phys., 2006)
3rd International Conference on Molecular Electronics and Bioelectronics, Tokyo, JAPAN, MAR 03-04, 2005.

(untitled) - Kiyomura, T.; Nemoto, T.; Yoshida, K.; Minari, T.; Kurata, H.; Isoda, S. (Thin Solid Films, 2006)

(untitled) - Kakudate, T.; Yoshimoto, N.; Kawamura, K.; Saito, Y. (J. Cryst. Growth, 2007)

(untitled) - Wisz, G.; Kuzma, M.; Virt, I.; Sagan, P.; Rudyj, I. (Appl. Surf. Sci., 2011)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Anczykowski, B.; Gotsmann, B.; Fuchs, H.; Cleveland, J. P.; Elings, V. B. (Appl. Surf. Sci., 1999)